Integrating Clinical Intuition for a Whole Person Approach to Empowerment. - Sousa, Jennifer (International Journal of Transpersonal Studies, 2024)
This paper is a summary of a study utilizing constructivist grounded theory to examine the process of accessing and applying clinical intuition in psychotherapy. Intensive interviews were conducted with 19 psychotherapists to explore their experiences with clinical intuition, including training on the topic, supportive conditions for accessing intuition, and decision making around its application in session. Engagement in an iterative process of data collection and analysis occurred to arrive at the constructed theory: integrating clinical intuition for a whole person approach to empowerment. The theory is comprised of the core categories (a) building trust and confidence to access and use intuition as a therapist, (b) practicing, and (c) empowering clients to connect with their own intuition.